Dialogue and reciprocity in an international teaching practicum. Issue 2 (15th March 2017) - Parr, Graham; Faulkner, Julie; Rowe, Craig
ABSTRACT: Many teacher education institutions across the world are now initiating and supporting international teaching practicums to better prepare their teaching graduates to teach for diversity. Recently, some of these practicums have embedded service-learning structures and discourses to further encourage pre-service teachers (PSTs) to think beyond their self-interests towards larger ethical and educational questions. This paper employs narrative-based inquiry methods to explore the lived experiences of three co-leaders of an international teaching practicum in South Africa for Australian PSTs underpinned by dialogic service-learning principles. Using Bakhtinian dialogic theory, the authors generate alternative interpretations of reflective narratives they have written, in order to examine the concepts of dialogue and reciprocity in their lived experience of this teaching practicum. The authors conclude that reciprocity and dialogue are indeed valuable discourses for critically researching international teaching practicums with service-learning dimensions, but counsel against romanticising either of these.